Human resource management motivational strategies for enhancing business educators’ job performance in tertiary institutions in Edo and Delta states, Nigeria - Robinson Osarumwense Owenvbiugie; Roseline Efosa Ekhaise (Intelektual Pustaka Media Utama, 2020)
The study assessed human resource management strategies for enhancing employees’ motivation in Edo State. Four research questions guided the study. The study size was 182 business educators in tertiary institutions in Edo and Delta States. The descriptive survey design was used for this study. The instrument used was validated by three experts. Pearson’s Product Moment Correlation coefficient was used to compute reliability of the instrument which yielded a correlation coefficient of 0.71. Data collected were analyzed using descriptive statistics. Means were used to answer all the research questions. From the results of the analysis, it was discovered that employers empowered their employees to very low extent; employers rewarded their employees to high extent; employers redesigned employees’ jobs to low extent, and employers created flexible jobs for their employees to low extent respectively. Consequently, it was recommended that workers should be sufficiently empowered to enhance higher performance and more productive. This will also go a long way to reduce attrition rate, the use of verbal praise, allowing workers’ personal development should be given priority attention by management to enhance higher productivity, management should redesign tasks/jobs from time to time so as to enhance motivation, job satisfaction, commitment to reduce absenteeism and turnover, among others.